Increased water use efficiency in miR396-downregulated tomato plants. (February 2021) - Fracasso, Alessandra; Vallino, Marta; Staropoli, Alessia; Vinale, Francesco; Amaducci, Stefano; Carra, Andrea
Highlights: In drought conditions miR396-downregulated plants transpire less water than WT. In miR396-downregulated tomato plants jasmonate and GABA pathways are activated. Tomato plants downregulated for miR396 have increased WUE under water stress. Abstract: MicroRNAs regulate plant development and responses to biotic and abiotic stresses but their impact on water use efficiency (WUE) is poorly known. Increasing WUE is a major task in crop improvement programs aimed to meet the challenges posed by the reduction in water availability associated with the ongoing climatic change. We have examined the physiological and molecular response to water stress of tomato ( Solanum lycopersicum L.) plants downregulated for miR396 by target mimicry. In water stress conditions, miR396-downregulated plants displayed reduced transpiration and a less then proportional decrease in the photosynthetic rate that resulted in higher WUE. The increase in WUE was associated with faster foliar accumulation of abscisic acid (ABA), with the induction of several drought-protective genes and with the activation of the jasmonic acid (JA) and γ-aminobutyric acid (GABA) pathways. We propose a model in which the downregulation of miR396 leads to the activation of a complex molecular response to water stress. This response acts synergistically with a set of leaf morphological modifications to increase stomatal closure and preserve the efficiency of the photosynthetic activity, ultimately resulting in higher WUE.